Integration Of Computer-Assisted Translation (Cat) Tools In The Curricula Of Translator Training Programmes In The Omani Context - Shallal, Isamaddin Mahmoud (2018)
As Computer Assisted Translation (CAT) tools have become one of the essential elements in the modern translator’s profile, it is important to equip student translators with this essential competence before joining the professional field. Accordingly, translator training programmes should include CAT tools training in their curricula. While this has been responded to by several translator training programmes, such as western developed countries, it is not clearly seen in the curricula of translator training programmes in Oman. This study investigated the current status of CAT tools training in the Omani translation curricula. It explored the cultural, economic and technical factors in addition to the other associated constructs, which represent significant elements with major impacts on the integration of CAT tools training in translation curricula. This work is a qualitative research, a multiple case study design, where five translator training institutions in Oman were studied as separate cases under the umbrella of the Omani translation education sector to form a multiple case study. The theoretical framework of the study made use of the concepts of the Diffusion of Innovation theory to answer the research questions and achieve the objectives. The study found that there are some attempts to integrate CAT tools training in the Omani translation curricula, but they are still incomplete, they need to be revised and reformulated. Moreover, as one of its objectives is to provide a suitable set of CAT tools to train Omani students on translation technology practices, the study provided constructive suggestions for this purpose built on the perspectives and views of the stakeholders in the studied contexts. Finally, although the study is limited to the Omani translation setting, the results can be suitable to replication in the other settings that share the Omani translation education setting the same characteristics.